STRAIGHTMORPH: A Voice Morphing Tool for Research in Voice Communication Sciences [version 2; peer review: 2 approved, 1 approved with reservations] - P Belin; H Kawahara (Open Research Europe)
The purpose of this paper is to make easily available to the scientific community an efficient voice morphing tool called STRAIGHTMORPH and provide a short tutorial on its use with examples. STRAIGHTMORPH consists of a set of Matlab functions allowing the generation of high-quality, parametrically-controlled morphs of an arbitrary number of voice samples. A first step consists in extracting an ‘mObject’ for each voice sample, with accurate tracking of the fundamental frequency contour and manual definition of Time and Frequency anchors corresponding across samples to be morphed. The second step consists in parametrically combining the mObjects to generate novel synthetic stimuli, such as gender, identity or emotion continua, or random combinations. STRAIGHTMORPH constitutes a simple but efficient and versatile tool to generate high quality, parametrically controlled continua between voices – and beyond.